A journey towards pediatric gastrointestinal endoscopy and its training: a narrative review - Luca Scarallo; Luca Scarallo; Giusy Russo; Sara Renzo; Paolo Lionetti; Paolo Lionetti; Salvatore Oliva (Frontiers Media S.A., 2023)
Background and aimsGastrointestinal (GI) endoscopy in pediatric setting has unique features and, therefore, requires an approach that is tailored to pediatric practice. There is still heterogeneity between training programs worldwide in terms of duration, number of procedures and assessment during and at the end of the training process.MethodsWe conducted a narrative review aiming to describe and summarize the existing literature on the various training methods for pediatric GI endoscopy to highlight the significance of specific pediatric endoscopy training.ResultsSimulation-based tools have been implemented in several training programs, providing a safer learning environment for trainees, especially in their earlier stages of training. Assessment of competence is gradually shifting from the sole evaluation of procedural numbers towards the development of more reliable and valid tools that can accurately measure technical competence. Despite such seismic shift, there is still a need for a standardized and comprehensive pediatric-oriented endoscopy curriculum that incorporates acquisition of procedural skills education and is built on the current competency-based model of training. All the above must sink their roots in trainees and to ensure that the endoscopists of tomorrow are capable of delivering high quality of care for children undergoing endoscopy.ConclusionIt is crucial to parallelly focus on the way trainers teach trainees. In this context, the implementation of "train the trainers" courses has improved important quality meters in GI endoscopy. Future research should put the focus on the potential subsequent favorable benefits of these changes on child health.